Akt Protein Kinase, miR-200/miR-182 Expression and Epithelial-Mesenchymal Transition Proteins in Hibernating Ground Squirrels - Lee, Yang-ja; Bernstock, Joshua D.; Klimanis, Dace; Hallenbeck, John M. (Frontiers in Molecular Neuroscience, 2018)
Hibernating 13-lined ground squirrels (Ictidomys tridecemlineatus) (TLGS) rank among the most brain hypoperfusion-tolerant mammals known. Herein we provide some evidence of cycling between an epithelial phenotype and a hybrid epithelial/mesenchymal (E/M) phenotype (partial EMT) within the brains of TLGS during each bout of hibernation torpor. During hibernation torpor, expression of the epithelial marker E-cadherin was reduced, while expression of the well-known mesenchymal markers vimentin and Sox2 were increased. P-cadherin, which has recently been proposed as a marker of intermediate/partial EMT, also increased during torpor, suggesting that a partial EMT may be taking place during hibernation torpor. Members of the miR-200 family and miR-182 cluster and Akt isoforms (Akt1, Akt2), well-known EMT regulators, were also differentially regulated in the TLGS brain during hibernation bouts. Using SHSY5Y cells, we also demonstrate that the Akt1/Akt2 ratio determined the expression levels of miR-200/miR-182 miRNA family members, and that these miRNAs controlled the expression of EMT-related proteins. Accordingly, we propose that such cell state transitions (EMT/MET) may be one of the mechanisms underlying the extraordinary ischemic tolerance of the TLGS brain during hibernation bouts; hibernator brain cells appear to enter reversible states that confer the stress survival characteristics of cancer cells without the risk of neoplastic transformation.